Features of the development of innovative systems in the foreign countries - Mamrayeva , D.G. (BUKETOV BUSINESS REVIEW, 2017)
In the article the priority directions of innovation policy development, legislation in the sphere of innovative activity support, innovation development support infrastructure, programs and measures of the development of innovation sphere, sources, volumes and mechanisms of state financing of innovative activity of foreign countries were investigated. The experience of scientific developments and technologies in the Netherlands, the Czech Republic, Japan, China, the United States and other countries has been studied. A comparative analysis of the state and development of foreign innovation systems was carried out. The factors hampering the development of innovation systems were indicated, in particular, the low share of business in financing scientific-research and development works; weak involvement of small businesses in innovation process; «brain drain»; territorial disparities in development; rapid aging of the population; high expenditures on the military-industrial complex; undeveloped venture capital markets; problems of commercialization of innovations; bureaucracy. Analysis of selected measures of state policy in different countries of the world, taking into account these shortcomings of innovation systems, made it possible to identify the several components of the state innovation policy that are used to develop the national innovation system: the creation of special organizations and bodies are responsible for identifying and implementing the innovation policies; and also active interaction with other countries in terms of technology exchange; creation of innovative clusters; implementation of major innovations in large transnational corporations; provision of free education; using of «innovative vouchers».